A Case of Terbinafine-Resistant Tinea Cruris Caused by Trichophyton tonsurans. (29th November 2021) - Firooz, Alireza; Lotfali, Ensieh; Fattahi, Mahsa; Fattahi, Maryam; Miramin Mohammadi, Akram; Shahrzad Kavkani, Mahshid
Abstract : A 26-year-old male patient referred to our center with a history of extremely itchy crusted skin lesions in his groins for one year. Moreover, his friend, a 25-year-old male, also developed similar lesions in the groin after using the shared pool, whose condition also did not improve with similar treatment. A regular mycology test (direct and culture test) was performed, as well as molecular examination. The antifungal susceptibility assay to terbinafine, itraconazole, posaconazole, fluconazole, and voriconazole was conducted according to the Clinical and Laboratory Standards Institute M38 third ed. The sequencing study identified T. tonsurans as the causative organism in both patients. The abovementioned organism isolated from both patients displayed resistance against terbinafine and fluconazole (MIC ≥ 4 µ g/ml and MIC ≥ 8 µ g/ml, respectively). Moreover, the susceptibility of both subjects to posaconazole (0.313 µ g/ml), voriconazole (0.25–0.0625 µ g/ml), and (1 µ g/ml) itraconazole increased. The present report aimed to emphasize the increase in antifungal resistance and a demand for antifungal stewardship, to control this public health threat.